OTS 2022 Sodobne informacijske tehnologije in storitve: Zbornik petindvajsete konference, Maribor, 7. in 8. september 2022 - Marina Bajić; Heričko, Marjan; Beranič, Tina (2022)
OTS 2022 Advanced Information Technologies and Services: Conference Proceedings of the Twenty-fifth Conference, Maribor, September 7th & 8th, 2022. The proceedings of the twenty-fifth conference OTS 2022 Advanced information technologies and services combine the experience and knowledge of the experts working and researching in the field of informatics. The articles cover successful approaches and good practices gained throughout multiple years of experience in different projects. The proceedings address topics connected with addressing the architectural challenges related to the introduction of artificial intelligence and machine learning, design and implementation of business intelligence solutions, efficient processing of big data and data streams, applying patterns in the design of microservice and serverless architectures, using the capabilities of blockchain technologies and decentralized applications, digital transformation and updates of ICT solutions based on functionality enabled by digital wallets, applying agile methods and improving responsiveness in providing effective support to business processes, system integration and development of smart home, telemedicine and green transition support services, development and optimization of mobile, online and cloud solutions, using the modern, including open source, technologies in the development of advanced information solutions and services.
Keywords: informatics; ICT technologies; software engineering; ICT solutions; digital transformation; development of mobile and web solutions; business intelligence; artificial intelligence and machine learning; processing of big data and data streams; agile methods; blockchain technologies; cybersecurity